Keatifitas dan Inovasi Pembelajaran dalam Pengembangan Kreatifitas Melalui Imajinasi, Musik, dan Bahasa - Rahayu, Nanik; Putri H, Saniyya; Masitha Nunlehu; Mia Sumiani Madi; Khalid, Nurbani (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
Creativity and innovation is a person's ability to develop or to generate new ideas or ideas that are useful for solving problems in everyday life. Children's creativity is very important to be developed from an early age. Several ways to develop creativity and also learning innovation in early childhood can be done through imagination, music and language. In creativity through imagination, children are invited to imagine, imagine and also demonstrate something that they think. By using several objects, children can imagine objects or themselves to be different figures. That way the development of children in creativity will be optimally stimulated. In musical creativity, children are invited to use objects or items that are around them in various ways so that they can produce sounds or tones which can then be combined with lyrics so that they become a rhythmic song. The development of creativity in the development of music can not only improve the artistic aspect, but also the child's thinking power of imagination that describes an object that becomes a musical instrument. In language creativity, children are invited to express their ideas or ideas by expressing them into an opinion. The development of children's creativity can be developed in various ways, of course through fun activities for children so that children can feel comfortable and can optimize their development. This article aims to describe the development of children's creativity and innovation through imagination creativity, musical creativity, and language creativity. The method used for data collection is in the form of a literature study, namely a method that can study various reference books and similar previous research results. Keywords: Learning Creativity, Imagination Creativity, Music Creativity, Language Creativity